New World Heterotermes (Isoptera, Rhinotermitidae): molecular phylogeny, biogeography and description of a new species - Carrijo, Tiago F.; Pontes-Nogueira, Matheus; Santos, Rafaella G.; Morales, Adriana C. [UNESP]; Cancello, Eliana M.; Scheffrahn, Rudolf H. (Wiley, 2020)
Heterotermes Froggatt is a subterranean termite genus consisting of 30 living described species worldwide, with nine occurring in the New World. Herein we provide a molecular phylogeny, using both mitochondrial and nuclear markers, of all New World species of Heterotermes, including biogeographical analysis, and describe a new species from Paraguay and Bolivia, based on morphological and molecular evidence. Our analysis recovered the New World species as paraphyletic to a monophyletic Australian clade. Within this New World + Australian clade, two monophyletic major groups were formed c. 28 Ma: the aureus- and tenuis-groups. The aureus-group has a disjunct and broad distribution consisting of two clades. The first clade extends into the Nearctic region and a second is composed of a branch in the Caatinga and Cerrado biomes (H. sulcatus Mathews) and a branch in the Chacoan biome (a new species, Heterotermes lauralinearum Carrijo sp.n.). The tenuis-group is composed of four broadly distributed Neotropical species and the Australian clade. A single dispersion event from South America to Australia probably occurred between 13 and 24 Ma. Heterotermes crinitus Emerson was the first to diverge, being sister group of all other species in the tenuis-group, followed by Heterotermes assu Constantino. An analysis of the historical biogeography of Heterotermes suggests that jump dispersal was the most important cladogenetic process for the genus. This study is the most comprehensive phylogeny of Heterotermes and contributes to the understanding of termite evolution and geographic distribution in the New World, complementing recent studies focused on worldwide patterns. This published work has been registered on Zoobank, http://zoobank.org/urn:lsid:zoobank.org:pub:8951A29B-8B69-4CD5-B9DF-2C70D4628D97.